2012
DOI: 10.1002/chem.201200694
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Quaternary Stereocenter Formation

Abstract: An efficient palladium catalyst is presented for the formation of benzylic quaternary stereocenters by conjugate addition of arylboronic acids to a variety of β,β-disubstituted carbocyclic, heterocyclic, and acyclic enones. The catalyst is readily prepared from PdCl(2), PhBOX, and AgSbF(6), and provides products in up to 99% enantiomeric excess, with good yields. Based on this strategy, (-)-α-cuparenone has been prepared in only two steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…18 However, we found that highly polar solvents failed to produce product (Table 4, entries 2 and 3). Switching to dicationic palladium by employing tetrakis acetonitrile palladium(II) tetrafluoroborate facilitated no conversion in methanol at a variety of temperatures (entries 4–6), or as a mixture with dichloroethane as cosolvent (entry 6).…”
Section: Development and Optimization Of Reaction Conditionsmentioning
confidence: 91%
“…18 However, we found that highly polar solvents failed to produce product (Table 4, entries 2 and 3). Switching to dicationic palladium by employing tetrakis acetonitrile palladium(II) tetrafluoroborate facilitated no conversion in methanol at a variety of temperatures (entries 4–6), or as a mixture with dichloroethane as cosolvent (entry 6).…”
Section: Development and Optimization Of Reaction Conditionsmentioning
confidence: 91%
“…77 A related palladium catalyzed conjugate addition of arylboronic acids to acyclic enones was reported but enantioselectivities were quite low (not shown). 78 …”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…Indeed, recent publications prove palladium-catalyzed conjugate addition to be a burgeoning field of research. 16 After the initial disclosure, we observed that in addition to catalyzing conjugate additions to 5-, 6-, and 7-membered enones, the Pd/PyOx catalyst successfully reacted with chromones and 4-quinolones. 17 Intrigued by the broad substrate scope and operational simplicity of this highly asymmetric process, we conducted a thorough study to optimize the reaction conditions, including measures to reduce the catalyst loading, lower the reaction temperature, and further generalize the substrate scope.…”
Section: Introductionmentioning
confidence: 98%